A 10-year retrospective study on primary and recurrent hidradenitis suppurativa - Alla, Mrinalini; Kiarie, Patrick; Bodden, Chloe; Aponte, Daphne Gonzalez; Janbey, Selma; Louis, Martine A.; Miele, Andrew; Mandava, Nageshwara (International Surgery Journal, 2024)
Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease characterized by follicular occlusion and apocrine gland inflammation. It is often misdiagnosis and delays, resulting in poor quality of life in some cases and severe consequences and poor patient outcomes. Limited literature compares presentation and treatment outcomes of recurrent HS, any information may aid clinicians in prompt diagnosis and treatment to alleviate the various challenges patients face and the complications from disease progression. Methods: A 10-year (2012-2022) retrospective chart review of the Epic Medisys database that analyzed patients admitted to flushing hospital center with a diagnosis of HS as a primary or secondary diagnosis at our community teaching hospital in Flushing, New York. Results: In our patient sample, HS was most commonly diagnosed in African-American and female patients under the age of 30 years. Common comorbidities included obesity. Antibiotics had the highest cure rate overall, and surgical interventions were more effective for recurrent disease. Conclusions: From our study we concluded that most patients were African American and female presenting younger than 30 years with axillary lesions most commonly characterized as nodules and abscesses. Antibiotics had the highest cure rate for both groups; with surgical intervention more effective from recurrent disease.